2016
DOI: 10.1159/000450993
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Frontal Activations at High Working Memory Load in Mild Cognitive Impairment: Near-Infrared Spectroscopy

Abstract: Background: Some functional magnetic resonance imaging studies have reported altered activations in the frontal cortex during working memory (WM) performance in individuals with mild cognitive impairment (MCI), but the findings have been mixed. The objective of the present study was to utilize near-infrared spectroscopy (NIRS), an alternative imaging technique, to examine neural processing during WM performance in individuals with MCI. Methods: Twenty-six older adults with MCI (7 males; mean age 69.15 years) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
64
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(69 citation statements)
references
References 74 publications
4
64
1
Order By: Relevance
“…Recent studies using near-infrared spectroscopy also indicated decreased frontal activation at high WM load in MCI cases and suggested an association between frontal hypoactivation and WM difficulties[13]. In the same line, an altered frontal lateralization that impact on verbal fluency performances in MCI cases was recently reported [37]. Moreover, MCI cases exhibit increased difficulties in modulating FPN activation that usually decreases after cognitive training to guarantee processing efficiency in healthy controls [38].…”
Section: Discussionmentioning
confidence: 91%
“…Recent studies using near-infrared spectroscopy also indicated decreased frontal activation at high WM load in MCI cases and suggested an association between frontal hypoactivation and WM difficulties[13]. In the same line, an altered frontal lateralization that impact on verbal fluency performances in MCI cases was recently reported [37]. Moreover, MCI cases exhibit increased difficulties in modulating FPN activation that usually decreases after cognitive training to guarantee processing efficiency in healthy controls [38].…”
Section: Discussionmentioning
confidence: 91%
“…However, individuals with mild cognitive impairment may produce decreased oxyhemoglobin concentrations. [38, 39] Thus it appears that using portable cognitive testing and neuroimaging methods such as fNIRS may help to document evolving cognitive impairments in at-risk populations living in the community.…”
Section: Discussionmentioning
confidence: 99%
“…The mean age of participants varied between 57-80 years, and few had an equal gender split between participants. All studies reported MMSE except four [15,64,68,69]. All participants had an MMSE >24, or equivalent, except one study (mean MMSE 23.7) [54].…”
Section: Summary Of Characteristics Of the Studiesmentioning
confidence: 99%
“…All studies lacked sample size calculations, and few demonstrated testing for validity and reliability ( Supplementary Figures 1 and 2). Twenty-two of the 26 studies were cross sectional [15,18,20,40,47,48,[53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69], and the remaining four studies were longitudinal [50][51][52]60] (two mixed design) [52,60]. Follow-up time in the longitudinal studies ranged from five weeks to two years [50][51][52]60].…”
Section: Summary Of Characteristics Of the Studiesmentioning
confidence: 99%
See 1 more Smart Citation